Functional roles of RNA-Binding Proteins in plant signaling - Muleya, Victor; Marondedze, Claudius (MDPI AG, 2021)
RNA-binding proteins (RBPs) are typical proteins that bind RNA through single or multiple RNA-binding domains (RBDs). These proteins have a functional role in determining the fate or function of the bound RNAs. A few hundred RBPs were known through in silico prediction based on computational assignment informed by structural similarity and the presence of classical RBDs. However, RBPs lacking such conventional RBDs were omitted. Owing to the recentmRNAinteractome capture technology based on UV-crosslinking and fixing proteins to their mRNA targets followed by a nity capture purification and identification of RBPs by tandem mass spectrometry, several hundreds of RBPs have recently been discovered. These proteome-wide studies have colossally increased the number of proteins implicated in RNA binding and unearthed hundreds of novel RBPs lacking classical RBDs, such as proteins involved in intermediary metabolism. These discoveries provide wide insights into the post-transcriptional gene regulation players and their role in plant signaling, such as environmental stress conditions. In this review, novel discoveries of RBPs are explored, particularly on the evolving knowledge of their role in stress responses. The molecular functions of these RBPs, particularly focusing on those that do not have classical RBDs, are also elucidated at the systems level.